Experimental Challenges in Studying Hydrogen Absorption in Ultrasmall Metal Nanoparticles - Zlotea, Claudia; Oumellal, Yassine; Provost, Karine; Ghimbeu, Camelia Matei (Frontiers in Energy Research, 2016)
Recent advances on synthesis, characterisation and hydrogen absorption properties of ultra-small metal nanoparticles (defined here as objects with average size ≤ 3 nm) are briefly reviewed in the first part of this work. The experimental challenges encountered in performing accurate measurements of hydrogen absorption in Mg- and noble metal-based ultra-small nanoparticles are addressed. The second part of this work reports original results obtained for ultra-small bulk immiscible Pd-Rh nanoparticles. Carbon supported Pd-Rh nanoalloys in the whole binary chemical composition range have been successfully prepared by liquid impregnation method followed by reduction at 300 °C. EXAFS investigations suggested that the local structure of these nanoalloys is partially segregated into Rh-rich core and Pd-rich surface coexisting within the same nanoparticles. Downsizing to ultra-small dimensions completely suppresses the hydride formation in Pd-rich nanoalloys at ambient conditions, contrary to bulk and larger nanosized (5-6 nm) counterparts. The ultra-small Pd90Rh10 nanoalloy can absorb hydrogen forming solid solutions under these conditions, as suggested by in situ XRD. Apart from this composition, common laboratory techniques such as, in situ XRD, DSC and PCI failed to clarify the hydrogen interaction mechanism : either adsorption on developed surfaces or both adsorption and absorption with formation of solid solutions. Concluding insights were brought by in situ EXAFS experiments at synchrotron: ultra-small Pd75Rh25 and Pd50Rh50 nanoalloys absorb hydrogen forming solid solutions at ambient conditions. Moreover, the hydrogen solubility in these solid solutions is higher with increasing Pd content and this trend can be understood in terms of hydrogen preferential occupation in the Pd-rich regions, as suggested by in situ EXAFS. The Rh-rich nanoalloys (Pd25Rh75 and Pd10Rh90) only adsorb hydrogen on the developed surface of ultra-small nanoparticles. In summary, in situ characterization techniques carried out at large scale facilities are unique and powerful tools for in-depth investigation of hydrogen interaction with ultra-small nanoparticles at local level.